Necroptosis-related lncRNA in lung adenocarcinoma: A comprehensive analysis based on a prognosis model and a competing endogenous RNA network - Mao, Fuling; Li, Zihao; Li, Yongwen; Huang, Hua; Shi, Zijian; Li, Xuanguang; Wu, Di; Liu, Hongyu; Chen, Jun (Frontiers in Genetics, 2022)
Background: Necroptosis, an innovative type of programmed cell death, forms necrosomes and eventually mediates necrosis. Multiple lines of evidence indicate that necroptosis plays a major role in human cancers. However, the contribution of necroptosis to lung adenocarcinoma (LUAD) remained unclear. Methods: The NRL signature was constructed in the training cohort and verified in the validation cohort and all cohorts based on TCGA database. Also, the nomogram was built. The tumor microenvironment (TME), Checkpoint, human leukocyte antigen (HLA), and m6A methylation levels between low-risk and high-risk groups were analyzed. Then we identified 5 truly prognostic lncRNAs (AC107021.2, AC027117.1, FAM30A, FAM83A-AS1, and MED4-AS1) and constructed a ceRNA network. And the 4 hub genes of downstream genes were discovered and analyzed using immune, pan-cancer, and survival analyses. Results: the prognosis of LUAD patients can be accurately predicted by this signature, and patients with poor risk scores were identified with an obvious “hot” immune infiltration level which strongly associated with a better prognosis. Based on ceRNA network, we believed that through CDK family proteins, NRL-associated lncRNAs regulated the TME of LUAD patients.